Parameters of service quality and its relationship with customer satisfaction in four-star accommodations in Mazatlan, Sinaloa, Mexico - Morales Morales, Jaime Josué; González Álvarez, Eleazar; Valdez Acosta, Nadia Aileen; Morales Morales, Jesús René (Unidad Editorial UPTC, 2021)
The objective of this study is to identify the most significant parameters that contribute to customer satisfaction based on the service provided to guests of a four-star hotel in the port of Mazatlán, Sinaloa, through a quantitative-descriptive and cross-sectional methodology. A survey was applied to a population of 100 guests with a sampling error of 1.89% using an instrument with a Cronbach's Alpha of 0.92 of reliability. Statistical cross-tabulation analysis was used to treat the data provided by the applied instrument and by means of Pearson's chi-square and the value of p = (0.05), it was possible to identify those 12 elements were considered to assess the satisfaction of the hotel guests, the results show that ten of them present a greater positive relationship on the variable to be explained called satisfaction, offering a quality of service as a result. Keywords: Customer satisfaction, quality of service, hotel sector. JEL codes: M31 Received: 26/10/2020. Accepted: 25/07/2021. Published: 01/12/2021.